Alleles of the Ly-17 alloantigen define polymorphisms of the murine IgG Fc receptor. - Holmes, K L (1985)
Antibodies specific for allelic determinants of the cell membrane alloantigen Ly-17 were found to react with genetically determined polymorphic sites on the murine IgG Fc receptor (Fc gamma R). Monoclonal antibodies specific for Ly-17.2 and the Fc gamma R detected identical populations of cells in thymus, spleen, lymph node, and bone marrow and had nearly identical reactivity with a large number of hematopoietic neoplasms. Antibodies to the Fc gamma R and either allele of Ly-17 blocked binding of rabbit IgG dimers to the Fc gamma R on spleen and bone marrow cells. Antibodies to the Fc gamma R also blocked binding of antibodies to either allele of Ly-17, whereas anti-Ly-17 antibodies only partially blocked the binding of antibodies to the Fc gamma R. Biochemical studies showed that antibodies to Ly-17 and the Fc gamma R precipitated proteins of Mr 55,000-60,000. The identity of the proteins recognized by these antibodies was confirmed by sequential immunoprecipitation.